A Short Introduction to Iranian Drama - Kazemimojaveri, Elmira (Mimesis Journal, 2016)
The purpose of this first study is to provide a broad overview of Iranian theater in three historical periods: the age of tradizions and rituals which were the first forms of theater, changes after the advent of Islam and finally effects of Constitutional Revolution and modernism. This process, lasting lasting for ages, is here summarized in a few pages.